PERSPECTIVES OF THE APPLICATION OF ARTIFICIAL INTELLIGENCE IN LOCAL SELF-GOVERNMENT IN THE REPUBLIC OF SERBIA - Stanković, Marko (Serbian political thought, 2025)
The paper analyses the use of artificial intelligence in the exercise of competences of local self-government in the Republic of Serbia. After the introductory considerations, which also include a short review of the legal framework of the AI in the Republic of Serbia, there is an analysis of different possibilities of using AI in the performance of communal activities in general. After that, there is a brief presentation of the concept of local self-government in Serbia and its shortcomings, and then the discussion about possibilities of applying AI in municipalities and cities in the Republic of Serbia, primarily bearing in mind their size and scope of competences. In the concluding considerations, the results of the research are summarized, with particular emphasis on three key points for the wider application of artificial intelligence in local self-government in the Republic of Serbia in the future.